HISTORICAL WOMEN’S COSTUME OF KARAKALPAKSTAN: THE ROLE OF TRADITIONS IN THE FORMATION OF CURRENT FASHION TRENDS IN CLOTHING - Djadigerova, Bibiaysha (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article presents a comprehensive, multifaceted, and in-depth study of the artistic, aesthetic, technological, and semantic characteristics of historical Karakalpak women’s costume. The research aims at their scientific revitalization and practical integration into contemporary utilitarian fashion design. In an era of pervasive globalization and the homogenization of style within the fashion industry, the preservation and transmission of local cultural identity are of critical importance. Drawing upon fundamental ethnographic works by A. Allamuratov and I. Bogoslovskaya, as well as the collections of the State Museum of Local Lore of the Republic of Karakalpakstan, the author performs a detailed art-historical analysis of decorative composition, structural architectonics, and the cross-cultural dimensions of Karakalpak ornamentation. The study deconstructs key traditional garments (kiymeshek, kok-koylek, zhegde) and manual embroidery techniques. Based on this research, conceptual methods for adapting Karakalpak ethno-cultural heritage to the modern fashion industry are proposed (as demonstrated through the Aisha Couture brand), emphasizing manual craftsmanship and exclusive design over mass production.